Unravelling the myths of R0 in controlling the dynamics of COVID-19 outbreak: A modelling perspective. (September 2020) - Mohd, Mohd Hafiz; Sulayman, Fatima
Highlights: SIRS model with limited resources is used to investigate the COVID-19 pandemic. The transmission dynamics are examined using daily confirmed cases in Malaysia. In some cases, the outbreak occurs when basic reproduction number (R0) larger than 1. Even when R0 is less than 1, outbreak could still occur via alternative stable states. Consequently, rebound effect could emerge and infected cases rise much further. Abstract: COVID-19 is an emerging and rapidly evolving pandemic around the world, which causes severe acute respiratory syndrome and results in substantial morbidity and mortality. To examine the transmission dynamics of COVID-19, we investigate the spread of this pandemic using Malaysia as a case study and scrutinise its interactions with some exogenous factors such as limited medical resources and false detection problems. To do this, we employ a simple epidemiological model and analyse this system using modelling and dynamical systems techniques. We discover some contrasting findings with respect to the observations of basic reproduction number: while it is observed that R 0 seems to provide a good description of transmission dynamics in simple outbreak scenarios, this quantity might mislead the assessment on the severity of pandemic when certain complexities such as limited medical resources and false detection problems are incorporated into the model. In particular, we observe the possibility of a COVID-19 outbreak through bistable behaviour, even when the basic reproduction number is less than unity. Based on these findings, we caution policy makers not to make their decisions solely based on the guidance of the basic reproduction number only, which clearly could cause trouble.